2013
DOI: 10.1163/1568539x-00003111
|View full text |Cite
|
Sign up to set email alerts
|

Dominance and geographic information contained within black-capped chickadee (Poecile atricapillus) song

Abstract: In songbirds, male song is an acoustic signal used to attract mates and defend territories. Typically, song is an acoustically complex signal; however, the fee-bee song of the black-capped chickadee is relatively simple. Despite this relative simplicity, two previous studies (Christie et al., 2004b; Hoeschele et al., 2010) found acoustic features within the fee-bee song that contain information regarding an individual’s dominance rank; however each of these studies reported a different dominance-related acoust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
22
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 53 publications
4
22
1
Order By: Relevance
“…We changed the start frequency of the fee note to match the start frequency of the fee note that was being replaced in the song using the 'sliding time scale/pitch shift' effect in Audacity 1.3.12 (http://audacity.sourceforge.net). This manipulation resulted in songs with a mean ± SD internote interval frequency ratio of 1.13 ± 0.036 (range 1.07-1.186), which corresponds to the internote interval ratios found in a larger sample of songs (N = 360) from these two geographical locations (mean ± SD =1.13 ± 0.022; range1.047-1.206; Hahn et al, 2013a) and corresponds to the average internote interval ratio reported previously (i.e. 1.13; Weisman et al, 1990).…”
Section: Acoustic Stimulisupporting
confidence: 58%
See 4 more Smart Citations
“…We changed the start frequency of the fee note to match the start frequency of the fee note that was being replaced in the song using the 'sliding time scale/pitch shift' effect in Audacity 1.3.12 (http://audacity.sourceforge.net). This manipulation resulted in songs with a mean ± SD internote interval frequency ratio of 1.13 ± 0.036 (range 1.07-1.186), which corresponds to the internote interval ratios found in a larger sample of songs (N = 360) from these two geographical locations (mean ± SD =1.13 ± 0.022; range1.047-1.206; Hahn et al, 2013a) and corresponds to the average internote interval ratio reported previously (i.e. 1.13; Weisman et al, 1990).…”
Section: Acoustic Stimulisupporting
confidence: 58%
“…Although the black-capped chickadees' range extends across most of North America (Smith, 1991), little geographical variation has been described in this song (although, variation has been found in geographically isolated populations of chickadees, where some animals produce unusual songs; see Gammon & Baker, 2004;Kroodsma et al, 1999). Recently, Hahn et al (2013a) conducted a bioacoustic analysis on songs produced by birds from different geographical locations (northern British Columbia and eastern Ontario). For this bioacoustic analysis, six acoustic features were analysed, similar to previous bioacoustic analyses of fee-bee songs (e.g.…”
mentioning
confidence: 99%
See 3 more Smart Citations